An enzyme-assembled gel monolithic microreactor for continuous flow asymmetric synthesis of aryl alcohols. Issue 24 (14th October 2022) - Chen, Qiang; An, Yuchao; Feng, Mingjian; Li, Jincheng; Li, Yanjie; Tong, Feifei; Qu, Ge; Sun, Zhoutong; Wang, Yujun; Luo, Guangsheng
Abstract : For the first time, a porous gel-monolithic microreactor with high catalytic-activity and stability was developed via in situ assembling of alcohol-dehydrogenase. Abstract : Green, efficient, and sustainable flow synthesis of intermediate chiral aryl alcohols is critical for continuous drug-manufacturing. Enzyme immobilization endows flow biocatalysis with higher application potential; however, conventional methods are limited by cumbersome operations, a trade-off between activity and stability, and low loading due to the required support. Here, for the first time, we demonstrated the microfluidic induction of alcohol dehydrogenase to form enzyme-assembled gels (EAGs) in a microreactor, with controllable mechanical properties and a porous architecture. Six chiral aryl alcohols were successfully synthesized by this approach in flow asymmetric reduction. Moreover, the support-free EAG was capable of in situ flow immobilization and reversible de-immobilization without reactor disassembly. The EAG monolithic microreactor presented an excellent space–time yield of 88.05 g L −1 h −1 and a high total turnover number of 62 600 after 100 h of operation (over 1300 reactor volumes), highlighting its high activity and stability.